2019
DOI: 10.1186/s12941-019-0308-y
|View full text |Cite
|
Sign up to set email alerts
|

Frugivorous bats in the Colombian Caribbean region are reservoirs of the rabies virus

Abstract: BackgroundBats are an important ecological group within ecosystems. The rabies virus is a Lyssavirus, and haematophagous bats are the principal reservoir; however, the virus has also been detected in non-haematophagous bats. The objective was to determine the rabies virus in non-haematophagous bats in the Colombian Caribbean region.MethodsIn 2017, a cross-sectional study was carried out with a base-risk sampling in twelve geographic zones of the Colombian Caribbean area that included the main ecosystems of two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 38 publications
0
8
0
1
Order By: Relevance
“…A 3.5% MERS CoV infection rate (n = 29; 95% CI 0-20%) in Taphozous perforatus bats is low compared with that for severe acute respiratory syndrome-like CoV in rhinolophid bats in China (10%-12.5%) but consistent with CoV prevalence among bats in Mexico (Anthony et al, 2013;Memish et al, 2013). Bats are reservoirs of several viruses that can cause human disease, including rabies, Hendra, Nipah, Marburg, severe acute respiratory syndrome CoV, Ebola, rabies, and even some arboviral diseases, such as dengue and Venezuelan Equine Encephalitis viruses (Calderon, Guzman, Mattar, Rodriguez, Acosta, et al, 2019;Lau et al, 2005;W. Li et al, 2005;Memish et al, 2013;Poon et al, 2005;Smith & Wang, 2013).…”
Section: Discussionmentioning
confidence: 69%
“…A 3.5% MERS CoV infection rate (n = 29; 95% CI 0-20%) in Taphozous perforatus bats is low compared with that for severe acute respiratory syndrome-like CoV in rhinolophid bats in China (10%-12.5%) but consistent with CoV prevalence among bats in Mexico (Anthony et al, 2013;Memish et al, 2013). Bats are reservoirs of several viruses that can cause human disease, including rabies, Hendra, Nipah, Marburg, severe acute respiratory syndrome CoV, Ebola, rabies, and even some arboviral diseases, such as dengue and Venezuelan Equine Encephalitis viruses (Calderon, Guzman, Mattar, Rodriguez, Acosta, et al, 2019;Lau et al, 2005;W. Li et al, 2005;Memish et al, 2013;Poon et al, 2005;Smith & Wang, 2013).…”
Section: Discussionmentioning
confidence: 69%
“…1 ). Interestingly, rabies transmission has also been noted between these species and is potentially explained by their frequent ecological overlap together with their evolutionary relatedness within the family Phyllostomidae 45 , 46 . Given our low sample size for A. lituratus , further instances of cross-species transmission may be found, and this also holds true for other species of bats within Phyllostomidae that roost with D. rotundus and were poorly sampled, such as G. soricina .…”
Section: Discussionmentioning
confidence: 99%
“…A Colombian study performed on 286 brains from bats of six families and 23 species showed that two species, Artibeus lituratus and Artibeus planirostris , were positive for the rabies virus ( Calderon et al, 2019a ). Another study conducted in Chile reported that 9.5% of 15,000 bats captured were naturally infected ( Escobar et al, 2015 ).…”
Section: Role Of Bats In the Origin Of Emerging And Re-emerging Infecmentioning
confidence: 99%
“…As a consequence of the destruction of natural habitats, closer interaction between bats and humans has grown significantly, especially in mining areas ( Bonilla-Aldana et al, 2019 ). Rabies transmission primarily occurs via direct bites or scratches from infected bats ( Calderon et al, 2019a ); secondary transmissions in humans takes place through contact with infected pets. These viruses cause acute progressive encephalitis that is inevitably fatal from the onset of clinical signs.…”
Section: Role Of Bats In the Origin Of Emerging And Re-emerging Infecmentioning
confidence: 99%